2021
DOI: 10.1111/1742-6723.13810
|View full text |Cite
|
Sign up to set email alerts
|

Benign paroxysmal positional vertigo in the emergency department: An observational study of an Australian regional hospital's acute clinical practice

Abstract: Objective To analyse adherence to evidence based practice in the diagnosis and treatment of benign paroxysmal positional vertigo (BPPV) in a regional ED. Methods Retrospective observational population study. Wyong Hospital's ED, Central Coast Local Health District, New South Wales, Australia. Medical records of patients with an ED diagnosis of BPPV (n = 101) between 2017 and 2018 were included for auditing. Adherence to clinical practice guidelines for BPPV4 statements 1a, 3a, 4a and 6 were reviewed as primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…The majority of patients presenting with BPPV in our study were discharged home. This is within the range reported in the literature that includes a high of 24% in Australia [ 3 ] and a low of 6% in Berlin [ 6 ]. The multivariable analysis showed that patients older than 54 years old were about five times more likely to be admitted to the hospital.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The majority of patients presenting with BPPV in our study were discharged home. This is within the range reported in the literature that includes a high of 24% in Australia [ 3 ] and a low of 6% in Berlin [ 6 ]. The multivariable analysis showed that patients older than 54 years old were about five times more likely to be admitted to the hospital.…”
Section: Discussionsupporting
confidence: 88%
“…Dizziness could indicate a wide range of disorders from benign, yet disruptive ear problems such as vertigo, to serious neurological problems such as stroke. Vertigo is characterized by frequent, irritating and curable symptoms that could have central or peripheral causes with peripheral ones accounting for around 60% of all vertigo cases [ 2 , 3 ]. While vestibular migraine is the most common cause of episodic vertigo [ 4 ], benign paroxysmal positional vertigo (BPPV) is the primary cause of peripheral vertigo with a lifetime prevalence of 36%, lifetime incidence of 2.4% and an annual incidence of 0.6% [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-intervention data sets were statistically compared to re-analysed pre-implementation control data set first reported by our group Neely et al 5 Data were analysed using the Adjusted Wald Technique to calculate 95% CIs. Descriptive statistics were cross-analysed through Minitab (Minitab 19.2020.1 LLC) using a two-sample percentage defective test for pre vs post.…”
Section: Discussionmentioning
confidence: 99%
“…4 diagnosed and managed within Australian EDs. 5,6 In a recent observational study this group found that only 45% (95% confidence interval [CI] 35-54%) were diagnosed using correct tests and 31% (95% CI 23-41%) received the gold-standard treatment. 5 We aimed to synthesise current best available evidence surrounding the differential diagnosis of acute dizziness for use in Wyong Public Hospital (WPH) ED.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation